Prevalence of clostridium difficile infection in Hospital Sungai Buloh and the associated risk factors / Nurul Suhaiza Hassanudin - Nurul Suhaiza, Hassanudin (2017)
Clostridium difficile infection (CDI) is the major recognized cause of nosocomial diarrhoea. It causes mild to severe diarrhoea and also pseudomembranous colitis. One of the most important risk factors for CDI is prior antibiotic exposure.Data on CDI among malaysian patients are still very limited. We aim look at the prevalence of CDI among inpatients of Hospital ungai Buloh. This study involved data collection of the stool specimens from 198 patients suspected to have CDI. The presence of Toxin A and Toxin B was tested by a commercial immunochromatographic rapid test kit (Duo Toxin A+B Check- 1 by VEDALAB-France), followed by culture for C. difficile. Secondary data were collected from the patients' medical records to determine demographic data, clinical presentations and associated risk factors. The prevalence of CDI among our patients was 6.1 %, and majority of the patients were male. The most common presentations, apart from diarrhoea, were fever, abdominal pain and nausea. Leucocytosis, dehydration and electrolyte imbalances were the common signs. The median length of stay was 16 day. The most common preceding antibiotic was amoxycillin. All of our patients were nursed in double or more occupancy room. Eight (66.7%) had history of admission to long-term healthcare facilities within the past 1 year and l 0 (83.3%) of the CDT patient were hypoalbuminaemic. In conclusion, the prevalence of CDI in Hospital Sungai Buloh is relatively low.